Observational, student, and teacher perspectives on interpersonal teacher behavior: Shared and unique associations with teacher and student emotions. (June 2021) - Donker, Monika H.; van Vemde, Lian; Hessen, David J.; van Gog, Tamara; Mainhard, Tim
Abstract: Teachers' interpersonal behavior in class is important for teacher and student emotions. Often the same rater (either teacher or students) is used to assess both perceptions of teacher behavior and emotions, which makes it vulnerable to common-method bias. Including other perspectives on teacher behavior has been proposed as a solution, but it is unclear to what extent different perspectives are correlated and how to separate their shared and unique variance in explaining emotions. Behavior of 80 teachers was rated from three perspectives (observers, students, and teachers) in terms of Agency (i.e., social influence) and Communion (i.e., friendliness). The three perspectives overlapped more strongly for teacher agency than for communion. Especially for students, teacher communion was a stronger predictor of emotions than agency. Our innovative statistical approach showed that the strong association between ratings of teacher behavior and emotions of the same rater are unlikely to result from common-method bias only. Highlights: Teacher agency and communion in class were evaluated from three perspectives. External observation, student ratings, and teacher self-report were included. The perspectives overlapped more strongly for teacher agency than for communion. Especially for students, communion was a better predictor of emotions than agency. We separated shared and unique variance of the perspectives in explaining emotions.